Typical Cell Signaling Response to Ionizing Radiation: DNA Damage and Extranuclear Damage - Yu, Hui (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
To treat many types of cancer, ionizing radiation (IR) is primarily used as external-beam radiotherapy, brachytherapy, and targeted radionuclide therapy. Exposure of tumor cells to IR can induce DNA damage as well as generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) which can cause non-DNA lesions or extracellular damage like lipid perioxidation. The initial radiation-induced cell responses to DNA damage and ROS like the proteolytic processing, as well as synthesis and releasing ligands (such as growth factors, cytokines, and hormone) can cause the delayed secondary responses in irradiated and unirradiated bystander cells through paracrine and autocrine pathways.